Penerapan Model Pembelajaran Number Heads Together Dalam Meningkatkan Hasil Belajar IPS Siswa Kelas IV Sekolah Dasar - Risal M. Merentek; Fransiska R. Korompis; Sarah S. N. Tombokan; Fonny Katili (Peneliti.net, 2023)
This study aims to improve IPS learning outcomes through the application of the Number Heads Together (NHT) learning model. The research was conducted using the Number Heads Together learning model. The research subjects were 17 grade IV students of GMIM KOYA Elementary School consisting of 10 female students and 7 male students. Data collection techniques used are observation and tests. The data analysis technique used is percentage and analysis techniques according to complete and incomplete categories through written tests, student interaction during learning, and student attitudes in the learning process. by implementing the Number Heads Together learning model. It is recommended that elementary school teachers apply the Number Heads Together learning model to improve social studies learning in elementary schools.